CONDITIONS OF FORMATION OF URANIUM MINERALS IN THE OXIDATION ZONE OF URANIUM DEPOSITS - Belova L.N.; Doynikova O.A. (My University, 2003)
The first generalization of materials on the oxidation zones of uranium deposits was done by L.N. Belova in her doctoral thesis in 1970. A unique and up to now the only classification of oxidation zones in hydrothermal uranium deposits was published in a monograph by her in 1975. Later on, Belova (2000) summed up her own observations on 40 uranium deposits of different scale and industrial-genetic types occurring, within the territory of the Commonwealth of Independent States (CIS) and Bulgaria; in addition, she analyzed all published data available at that time related to the formation of oxidation zones and accumulation of uranium minerals in the hypergenesis zone. On this basis, she classified in a general system of ore exogenic uranium accumulations.